Cuproptosis-related MTF1 inhibits kidney renal clear cell carcinoma progression by suppressing proliferation and regulating immune cell infiltration - Weipu Mao; Zhou Ding; Keyi Wang; Ming Chen (Compuscript Ltd, 2023)
Cuproptosis is a newly identified specific form of programmed cell death. Our study aimed to identify cuproptosis-related genes (CRGs) in patients with kidney renal clear cell carcinoma (KIRC) from the The Cancer Genome Atlas database and to evaluate CRG biological functions. Using lasso regression, we identified four KIRC prognosis-associated CRGs and constructed an associated prognostic risk signature. Kaplan-Meier curves showed that patients with high-risk scores had significantly lower survival times than patients with low-risk scores. Multivariate Cox analysis identified MTF1 and FDX1 as two independent overall survival CRGs. Moreover, qRT-PCR showed that MTF1 and FDX1 expression was downregulated in KIRC and knockdown of MTF1 and FDX1 significantly promoted KIRC cell proliferation and migration ability. In addition, the MTF1 level was positively correlated with immune cell infiltration and knockdown of MTF1 promoted tumor growth in vivo . We developed a signature of prognostic risk-associated CRGs that accurately predicted the prognostic status of KIRC patients. MTF1 and FDX1 were shown to be key CRGs. MTF1 acts as a tumor suppressor, and may be involved in the progression of KIRC by inhibiting proliferation and regulating immune cell infiltration.